Antibacterial Activity of (+) Usnic Acid against Multi Drug Resistant Acinetobacter baumannii from Clinical Isolates (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acinetobacter baumannii (Ab) is developing resistance to a variety of common antibiotics. and becomemultidrug resistant, extreme drug resistant, and pan drug resistant pathogens, requiring the identificationof new antibiotics as well as the identification of new plant compounds capable of acting against Ab.Recent research has revealed MDR Ab co-infections with COVID-19,, raising alarm bells. Sinceits isolation, Usnic acid has been investigated for a variety of pharmacological activities, includingantioxidant, antitumor, antibacterial, antifungal, antiviral, antiprotozoal, and insecticidal. ManyPlant-derived drugs show promising activity as new antimicrobial agents against multidrug resistant(MDR) strains. There is insufficient data to support the antibacterial activity of (+)-UA against MDRAcinetobacter baumannii..